Excellence in Innovation Management A Meta-Analytic Review on the Predictors of Innovation Performance - Sattler, Markus; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Innovation management is commonly understood as a central system and function of a firm$1 (Bs ability to keep up with developments in the market. Markus Sattler reviews the predictors of successful innovation management on firm level with a meta-analytic approach. His findings suggest that the role of knowledge management and an environment of learning are important success factors on which managers can have a substantial effect. Furthermore a clear managerial commitment to innovations and a sophisticated innovation process are further central predictors of a successful innovation management.s
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals